Synthesis and structural properties of (diamine)platinum(II) complexes of bis(alkylthio)methylenepropanedioic acid. Insight into bonding mode - Kim, KM; Lee, SS; Jung, OS; Jun, MJ; Sohn, YS (ELSEVIER SCIENCE SA LAUSANNE, 1997)
New (diamine) platinum(II) complexes of bis(alkylthio)methylenepropanedioate ligands, A(2)Pt(RS)(2)C=C(COO-)(2) (A = NH3 or A(2)=trans-(+/-)-1,2-diaminocyclohexane (DACH); R=CH3 or C2H5), have been prepared and structurally characterized both in the solid state and in solution. The crystal structures of a bis(ethylthio)methylenepropanedioate (BETMP) complex, (DACH)Pt(BETMP). 4H(2)O (monoclinic, P2(1), a=11.022(2), b=17.604(4), c=11.426(5) Angstrom, beta=93.42(3)degrees, V=2213(1) Angstrom(3), Z=4, R=0.065), and a bis(methylthio)methylenepropanedioate (BMTMP) complex, (DACH)Pt(BMTMP). 3H(2)O (triclinic, <P(1)over bar>, a=9.082(3), b=9.797(3), c=11.493(4) Angstrom, alpha=72.42(3), beta=74.28(3), gamma=84.93(3)degrees, V=938.4(5) Angstrom(3), Z=2, R=0.031), exhibit that among the possible chelating modes (O,O'-, O,S- and S,S'-), the present anionic ligands coordinate to the platinum(II) atom only in S,S'-chelating fashion. The band distances of Pt-S are in the range 2.273(2)-2.276(5) Angstrom. For the title complexes, the diethyl groups of the BETMP ligand occupy anti positions to each other whereas the dimethyl groups of the BMTMP ligand occupy syn positions in the solid state. However, NMR studies disclose that the BMTMP complexes exist as an isomeric mixture of syn and anti forms (1:2) in contrast to the retention of the anti isomeric form of the BETMP complexes in solution.